(untitled) (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
This comprehensive study investigates the crucial role of clauses in English sentence structure, primarily focusing on the distinction between independent clauses and dependent clauses. This research explores how these two types of clauses function as essential components in forming sentence structures, facilitating the expression of complex ideas and effective communication. The investigation reveals that independent clauses possess the ability to position alone as thorough sentences, while dependent clauses depend on independent clauses on the context and meaning. The study identifies various types of dependent clauses and examines how they contribute to more complex sentence structures. Furthermore, this research highlights the importance of subordinating conjunctions in introducing dependent clauses and establishing logical relationships within sentence structures. By elucidating the functions of independent and dependent clauses, this study provides valuable insights into the formation of effective sentence structures. The research demonstrates how the strategic use of independent and dependent clauses, along with the appropriate utilization of subordinating conjunctions, can enhance the quality and complexity of sentence structures. This analysis offers a deeper understanding of sentence structure mechanisms, contributing to broader linguistic theories and applications. The study emphasizes the critical role of clause analysis in developing strong writing skills and effective communication. The results indicate that a solid understanding of independent clauses, dependent clauses, and the use of subordinating conjunctions is crucial in creating varied and expressive sentence structures. This study contributes significantly to the considerate of sentence structures in English, underscoring the importance of independent clauses, dependent clauses, and subordinating conjunctions in language learning, teaching, and research. The study concludes that mastery of various clause types and the ability to combine them effectively are key to enhancing language proficiency and communication skills.